PERAN PEMERINTAH DALAM MENCEGAH TINDAKAN RADIKALISME MELALUI PENDIDIKAN MULTIKULTURAL - Eka Yanuarti; Asri Karolina; Devi Purnama Sari (POTENSIA: Jurnal Kependidikan Islam, 2019)
This study aims to find out how the role of government in preventing acts of radicalism through the application of multicultural education, this study uses library research. The results of this study indicate that there are 8 roles that can be applied by the government in preventing acts of radicalism through the application of multicultural education, namely first offering various curricula received from input from various groups. Second, providing various facilities so that students know about various cultures, Third, providing understanding of various cultures, Fourth selecting material that causes the emergence of acts of radicalism, Fifth minimizing social equality, Sixth maintaining unity and unity, Seventh supporting peace actions, Eighth participate in socializing in preventing acts of radicalism.